Pengaruh Social Media Marketing dan Brand Awareness Terhadap Keputusan Pembelian Pada Cafe Pitstop Gresik - Reynaldi Rizal Giovani; Sugeng Purwanto (REVITALISASI : Jurnal Ilmu Manajemen, 2022)
We want to shed light on how social media marketing and brand awareness influence consumers' purchase choices. “This study employs a quantitative and descriptive methodology. Customers of Cafe Pitstop Gresik make up the bulk of the study's sample. A sample of Cafe Pitstop Gresik customers who are at least 17 years of age, have social media accounts, and know Cafe Pitstop Gresik via social media is included in this research. Purposive sampling was utilized to gather the data, and 91 people took part in the survey. These values are above the necessary value of 0.70, which means that the study findings may be considered trustworthy. The composite reliability test yielded values for each variable of social media marketing (X1) 0, 902, brand awareness (X2) 0, 874, and purchase choices (X3) 0, 902. A quantitative descriptive research design, descriptive statistics and PLS analysis are all used in this study. According to the findings, social media marketing has a favorable and considerable impact on the purchase choices of customers. Brand awareness has a considerable impact on consumers' purchase choices, according to this study.”